STRATEGI PEMASARAN WEDDING ORGANIZER CAHAYA KASIH PELAMINAN DALAM MENINGKATKAN PENDAPATAN DI KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Olla Febiani; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2025)
This research is entitled "Marketing Strategy for Wedding Organizer Cahaya Kasih Pelaminan in Increasing Income in Kec. Lubuk Basung District. Agam” The aim of this research is to find out how the marketing strategy for the Wedding Organizer Cahaya Kasih Pelaminan increases income in the district. Lubuk Basung District. Agam. to analyze the extent of the application of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) faced by the company. The research method used in this research is qualitative descriptive research. In describing the research results, a SWOT matrix is used by analyzing internal and external factors which is carried out by providing a general description of the company's strengths, weaknesses, opportunities and threats. The results of the SWOT analysis show that the marketing strategy position of Cahaya Kasih Pelaminan Wedding Organizer is in increasing revenue in the district. Lubuk Basung District. Agam. is in Quadrant I, where the appropriate strategy to be implemented by the Cahaya Kasih Pelaminan Wedding Organizer in increasing income in the district. Lubuk Basung District. Agam. is an aggressive strategy by supporting aggressive growth policies.